Regulatory roles of indole-3-acetic acid in the physiological and biochemical responses of Cinnamomum camphora seedlings under cadmium stress - Jing Jiang; Chenyang Zhang; Meng Na; Shangqi Xu; Xiaoping Li; Shoubiao Zhou; Jihai Zhou (Ecotoxicology and Environmental Safety)
Soil cadmium (Cd) pollution has become increasingly severe, negatively affecting plant growth, soil safety, the ecological balance, and public health. Phytoremediation technology is an effective method for remediating soil Cd contamination because of its low cost, environmentally friendly nature, and minimal soil disturbance. However, phytoremediation efficiency is affected by factors such as the plant species, Cd concentration, and soil environment. In this study, a 180-day indoor potted experiment was conducted to explore the influences of various indole-3-acetic acid (IAA) levels on the growth, physiological and biochemical responses, Cd uptake, and soil enzyme activity of Cinnamomum (C.) camphora seedlings using 20 mg kg−1 Cd-contaminated soil with or without IAA treatments. The results showed that Cd stress significantly suppressed C. camphora seedling growth, whereas IAA application improved the basal diameter of seedlings by 22.22–133.33 %. This effect of IAA was observed primarily at low concentrations, while higher concentrations showed diminished effects. Compared to the Cd pollution treatment, adding 20 mg kg−1 IAA significantly enhanced the activities of antioxidant enzymes (SOD, POD, CAT), reduced the malondialdehyde (MDA) content, and decreased soil basal respiration (SBR). Moreover, IAA treatment promoted Cd uptake in the roots, stems, and leaves, and reduced the soil Cd content by 22.90–41.17 %. In conclusion, exogenous IAA addition effectively alleviates Cd stress by regulating the plant’s physiological and biochemical characteristics and soil enzyme activities. These findings suggest that the combined use of IAA and C. camphora represents a promising remediation method for soil heavy metal pollution.